Hematological characteristics and endocrine profiles of cloned dromedary camels (Camelus dromedaries) - Young-Bum Son; Mohammad Shamim Hossein; Yeon Ik Jeong; Mina Kang; Huijeong Kim; Yura Bae; Kung Ik Hwang; Alex Tinson; Singh Rajesh; Al Shamsi Noura; Woo Suk Hwang (Journal of Animal Reproduction and Biotechnology, 2024)
Background: Somatic cell nuclear transfer (SCNT) is a prominent technology that can preserve superior genetic traits of animals and expand the population in a short time. Hematological characters and endocrine profiles are important elements that demonstrate the stability of the physiological state of cloned animals. To date, several studies regarding cloned camels with superior genes have been conducted. However, detailed hemato-physiological assessments to prove that cloned camels are physiologically normal are limited. In this study, We evaluated the hemato-physiological characteristics of cloned male and female dromedary camels (Camelus dromedaries). Methods: Therefore, we analyzed variations in hematological characteristics and endocrine profiles between cloned and non-cloned age-matched male and female dromedary camels (Camelus dromedaries). Two groups each of male and female cloned and non-cloned camels were monitored to investigate the differences in hemato-physiological characteristics. Results: All the animals were evaluated by performing complete blood count (CBC), serum chemistry, and endocrinological tests. We found no significant difference between the cloned and non-cloned camels. Furthermore, the blood chemistry and endocrine profiles in male and female camels before maturity were similar. Conclusions: These results suggest that cloned and non-cloned camels have similar hematological characteristics and endocrine parameters.